2012
DOI: 10.4236/gsc.2012.22010
|View full text |Cite
|
Sign up to set email alerts
|

Composition of the Volatile Components Extracted from the Roots of <i>Scorzonera undulata</i> ssp <i>deliciosa</i> (Guiss) Maire: From Algeria

Abstract: The chemical composition of the volatile components of the dried roots of Scorzonera undulata ssp deliciosa collected from Algeria was determined by GC and GC/MS. The obtained results showed that the extracted oil contained nine fatty acids. The major compounds were hexadecanoic acid (42.2%), n-tetradecanoic acid (16.1%), 9-octadecenoic acid (7.7%) and 9-hexadecenoic acid (4.5%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 3 publications
1
3
0
Order By: Relevance
“…deliciosa. The role of these phytochemical components in counteracting oxidative stress, microbial and fungal growth, and many health disorders has been approved (Erden et al, 2013;Harkati et al, 2010;Mzid et al, 2017). Herein, halves of DPPH radical and the ferric reducing potential were inhibited at concentrations ranging from 0.1 to 0.25 mg × mL −1 that were close to what has been recently reported (Badraoui et al, 2020;Rahmouni et al, 2022).…”
Section: Discussionsupporting
confidence: 73%
“…deliciosa. The role of these phytochemical components in counteracting oxidative stress, microbial and fungal growth, and many health disorders has been approved (Erden et al, 2013;Harkati et al, 2010;Mzid et al, 2017). Herein, halves of DPPH radical and the ferric reducing potential were inhibited at concentrations ranging from 0.1 to 0.25 mg × mL −1 that were close to what has been recently reported (Badraoui et al, 2020;Rahmouni et al, 2022).…”
Section: Discussionsupporting
confidence: 73%
“…Fatty acid profiling studies on the genus are scarce. Recent literature review showed only a few studies subjecting fatty acids of the genus [21–25] . Species evaluated in these studies are Scorzonera paradoxa Fisch and CA Mey., S. undulata ssp deliciosa (Guiss) Maire, S. hieraciifolia Hayek., S. hispanica L., S. divaricata Turcz and S. tomentosa L. The results of the current study are in accordance with these studies which show that these species contain both saturated and unsaturated fatty acids namely oleic acid, linoleic acid, palmitic acid, stearic acid and myristic acid.…”
Section: Resultsmentioning
confidence: 99%
“…Other researchers have also shown that MeOH is a better solvent for extraction of flavonoids than other solvents such as EtOH, acetone, and DCM [27]. In addition, in a comparative study conducted by Ghasmezadeet et al [28] on the total flavonoid content of Scorzonera species the extraction capacity of MeOH was shown to be higher than that of acetone. Another study conducted to isolate and identify the flavonoids contained in nine taxa of Scorzonera species (S. austriaca Willd.…”
Section: Resultsmentioning
confidence: 92%